Temperature- and ontogeny-dependent metabolism in invasive early juvenile round goby (Neogobius melanostomus) - Herron, Hunter A.; Zarini, Sina; Thompson, William Andrew; Turko, Andy J.; Balshine, Sigal (Frontiers in Fish Science, 2025)
The round goby (Neogobius melanostomus) is the fastest spreading invasive fish in the Laurentian Great Lakes, and concurrent invasions are occurring globally. To inform management and mitigation strategies, metabolic rate of adult round goby has been rigorously quantified, but metabolism of the juvenile life stages represents an important knowledge gap. Here, we measured routine and maximum metabolic rates (RMR and MMR) of early juvenile round goby (mass 0.007–0.07 g, mean 0.02 g; total length 6.6–19.4 mm, mean 13.7 mm), ~100× smaller than any round goby measured previously. To understand how metabolism may be affected by a warming climate, we reared round goby at several ecologically relevant temperatures (15°C, 19°C, and 23°C) and a projected surface temperature under climate change scenarios (27°C). We tested early juveniles at two separate and distinct ages (6–7 weeks and 12–14 weeks post-hatch). Growth was highest at 23°C compared to 15°C and 27°C, but this pattern only emerged after 12–14 weeks of development. Routine metabolic rates increased over 2-fold between fish reared at 15°C vs. 27°C (Q10 = 1.98), but we found no clear difference in our estimation of the “scope for activity” (i.e., maximum—routine metabolic rate) across temperatures, suggesting a wide thermal performance curve. We also found that the bioenergetics models previously developed for adults do not effectively translate to juveniles; the current models underestimated observed RMR values by ~20–60% depending on temperature. Overall, data from this study can be used to improve bioenergetic modeling in the round goby by considering these earlier life stages and fill an important gap of knowledge in our understanding of an ecologically invasive species.